PENENTUAN POTENSI DAS MALABAR SEBAGAI DAERAH RESAPAN LAPANGAN PANASBUMI WAYANG WINDU DENGAN METODA NERACA AIR - Ramadhan Achmad, Dan
Wayang Windu is a geothermal field which has been utilized to generate 110 MW electricity. One of the important factors in managing geothermal resources is recharge area for geothermal reservoir, therefore, determination of recharge area is necessary to be conducted. Factors which controll recharge are climatology, hydrology, geology, and hydrogeology. This research is aimed to determine whether Malabar watershed, Pangalengan, Bandung Regency, has potential as recharge area for Wayang Windu’s reservoir, based on analysis of geology, hydrogeology, and water balance calculation. Geomorphologically, Malabar watershed is a volcanic footslope with gentle – moderate slope, and volcanic cone with steep – very steep slope. Stratigraphically, the area consists of volcanic rocks deposited in proximal facies, i.e. breccia-tuff, lapilituff, tuff, and pyroclastic breccia of Middle-Pliocene age, and in central facies, i.e. tuff in form of cinder cone. There are two faults in the research area, i.e.: northwest – southeast thrust fault, and north east – southwest strike slip. Groundwater in the area can be divided into two: groundwater in soil and groundwater in unconfined aquifer. Result of water balance calculation shows that in period of 20 – 26 of April, 2006, infiltration is 41.613 mm (64.79 % of total rain, i.e 64.229 mm). Of the infiltration, 2.193 mm (3.42 % from total rain) becomes groundwater flow and subsurface stormflow. The rest flows downward, to another watershed or sub-watershed, or flows to Wayang Windu’s reservoir. Therefore, it can be concluded that Malabar watershed has potential as a recharge area for Wayang Windu’s reservoir.